Islamic Art and Architecture - Hillenbrand, Robert (World of art, 2021)
Embracing over a thousand years of history and an area stretching from the Atlantic to the borders of India and China, this is an unrivalled synthesis of the arts of Islamic civilization. From the death of the Prophet Muhammad to the present day, Robert Hillenbrand traces the evolution of an extraordinary range of art forms, including architecture, calligraphy, book illumination, painting, ceramics, glassware, textiles and metalwork. New to this edition is a chapter ranging from c. 1700 to c. 1900, a period very often neglected in books on this subject. Hillenbrand explores how recent centuries, far from being a dark age, have seen incredible artistic ferment and creativity across the Islamic world. Full-colour illustrations of masterpieces of Islamic art and architecture - from Moorish Spain to contemporary Iran - show the far-reaching stylistic developments as well as the recurrent preoccupations that have shaped the arts of Islam since the seventh century.